Effects of post-harvest ‘ rubbing-sweating ‘ drying treatment on the accumulation of bioactive compounds in Codonopsis pilosula: a transcriptomic analysis - Liang, Wei; Bai, Gang; Sun, Jiachen; Tao, Wenzhen; Li, Qian; Dong, Pengbin; Wang, Hongyan; Cheng, Jiali; Guo, Fengxia; Chen, Yuan (Frontiers in Plant Science, 2025)
Postharvest processing critically determines the quality of Codonopsis pilosula, yet the molecular mechanisms underlying the traditional “rubbing–sweating” technique remain unclear. We hypothesized that rubbing–sweating imposes stronger abiotic stress than shade drying, thereby activating stress-responsive pathways and enhancing the accumulation of bioactive constituents. To test this, freshly harvested roots were processed by shade drying (SD) and rubbing–sweating drying (RD), and compared with fresh controls (FC) in terms of chemical composition, antioxidant enzyme activity, and transcriptomic profiles. After 6 days, RD significantly increased lobetyolin content by 15.3% relative to FC and 9.7% relative to SD (p<0.01), while polysaccharides reached 19.5% in RD versus 10.6% in FC (p<0.05). Antioxidant enzymes also exhibited marked increases under RD, with catalase activity elevated by 235% compared to FC. Transcriptome sequencing revealed 17,338 DEGs in RD vs. SD and 11,007 in RD vs. FC, enriched in MAPK signaling, hormone transduction, and aromatic amino acid biosynthesis. These findings support our hypothesis that rubbing–sweating enhances the medicinal quality of C. pilosula through stress-induced activation of metabolic pathways. This work provides the first transcriptomic evidence for the molecular basis of this traditional technique, offering new insights for optimizing and modernizing postharvest processing.